Apolipoprotein A-V Is a Novel Diagnostic and Prognostic Predictor in Pediatric Patients with Sepsis: A Prospective Pilot Study in PICU. (13th January 2020) - Wang, Chunxia; Cui, Yun; Miao, Huijie; Xiong, Xi; Dou, Jiaying; Shao, Lujing; Tang, Xiaomeng; Zhang, Yucai
Abstract : Background . Sepsis induces the release of lipid mediators, which control both lipid metabolism and inflammation. However, the role of serum apolipoprotein A-V (ApoA5) in sepsis is poorly understood in pediatric patients. Methods . ApoA5 was screened from serum proteomics profile in lipopolysaccharide- (LPS-) treated mice for 2 h, 24 h, and controls. Then, we conducted a prospective pilot study, and patients with sepsis admitted to a pediatric intensive care unit (PICU) were enrolled from January 2018 to December 2018. Serum ApoA5 levels on PICU admission were determined using enzyme-linked immunosorbent assays (ELISA). Blood samples from 30 healthy children were used as control. The correlation of ApoA5 with the clinical and laboratory parameters was analyzed. Logistic regression analyses and receiver operating characteristic curve (ROC) analysis were used to investigate the potential role of serum ApoA5 as a prognostic predictor for PICU mortality in pediatric patients with sepsis. Results . A total of 101 patients with sepsis were enrolled in this study. The PICU mortality rate was 10.9% (11/101). Serum ApoA5 levels on PICU admission were significantly lower in nonsurvivors with sepsis compared with survivors (P = 0.009 ). In subgroup analysis, serum levels of ApoA5 were significantly correlated with sepsis-associated multiple organ dysfunction syndrome (MODS) (P < 0.001 ), shock (P = 0.002 ), acute kidney injury (AKI) (P < 0.001 ), acute liver injury (ALI) (P = 0.002 ), and gastrointestinal (GI) dysfunction (P = 0.012 ), but not respiratory failure, brain injury, and pathogenic species (all P > 0.05 ). Correlation analyses revealed significant correlations of serum ApoA5 with Ca 2+ concentration. Remarkably, the area under ROC curve (AUC) for serum ApoA5 levels on PICU admission was 0.789 for prediction of PICU mortality with a sensitivity of 75% and a specificity of 84.5% at a threshold value of 822 ng/mL. Conclusions . Serum ApoA5 level is associated with sepsis-associated shock, AKI, ALI, GI dysfunction, or MODS in children. Moreover, the findings of the present study suggest a prognostic value of ApoA5 in children with sepsis, and lower serum ApoA5 than 822 ng/mL predicts worse outcome in pediatric sepsis.